2020
DOI: 10.3122/jabfm.2020.01.190284
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Changes to Existing Chronic Pain Management Plans

Abstract: Background:The objective of this qualitative study is to better understand primary care clinician decision making for managing chronic pain. Specifically, we focus on the factors that influence changes to existing chronic pain management plans. Limitations in guidelines and training leave clinicians to use their own judgment and experience in managing the complexities associated with treating patients with chronic pain. This study provides insight into those judgments based on clinicians' first-person accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Considering the economic aspect, superficial heat therapy has a nonrefundable individual cost which may represent a limit to its use as prevention. This aspect may also explain the absence of consensus on the statement further investigated in the survey on ''discontinuation or not of heat therapy after the resolution of pain,'' where the low compliance to pain treatment normally observed in clinical practice may also represent a reason not to propose the continuation of the treatment after resolution of symptoms [42][43][44]. The debate on the overall economic cost for the health care system of nonadherence to pain treatments is of great relevance nowadays, as nonadherence increases the cost for the system [45].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the economic aspect, superficial heat therapy has a nonrefundable individual cost which may represent a limit to its use as prevention. This aspect may also explain the absence of consensus on the statement further investigated in the survey on ''discontinuation or not of heat therapy after the resolution of pain,'' where the low compliance to pain treatment normally observed in clinical practice may also represent a reason not to propose the continuation of the treatment after resolution of symptoms [42][43][44]. The debate on the overall economic cost for the health care system of nonadherence to pain treatments is of great relevance nowadays, as nonadherence increases the cost for the system [45].…”
Section: Discussionmentioning
confidence: 99%
“…38 Prior to this study, we developed a Tx Tracker prototype based on a series of studies that identified primary care clinicians' information needs and decision-making challenges during visits by patients with chronic noncancer pain. 32 35 39 The prototype is an interactive application developed using the Axure prototyping tool ( ). While prior studies have evaluated decision support for opioid prescribing and chronic pain care, 40 41 42 this study is innovative because no prior evaluations focus on a tool to aid clinicians in choosing among many pain treatment options based on a presentation of past, current, and potential future treatments.…”
Section: Background and Significancementioning
confidence: 99%
“…25,[28][29][30][31] Furthermore, patients with chronic noncancer pain often bring, to their clinical visits, long and varied histories of symptoms, treatments tried, and goals and preferences for their care. Because patients' histories are complex and individuals' values and preferences vary, chronic pain care may benefit from EHR-based clinical decision support [32][33][34][35] that synthesizes and organizes key information, creating a structure that reduces time spent searching for and processing needed information. Moreover, this structure and time saving may allow primary care clinicians and their patients to engage more in shared decision making about pain treatment options.…”
Section: Background and Significancementioning
confidence: 99%